Efficacy of Antibiotics in Chronic Hematogenous Osteomyelitis in Children - Toirovich, Musayev Sodiqjon (Journal of Science in Medicine and Life, 2024)
Osteomyelitis is an inflammatory purulent bone disease that is accompanied by the destruction (destruction) of bone tissue and is caused by infection (bacteria, fungi). Children often suffer from osteomyelitis. The highest rate of the disease occurs at the age of 6-14 years, but the pathology also occurs in children under 1 year of age. With osteomyelitis, all bone structures are affected, as well as the surrounding soft tissues and bone marrow. The disease develops rapidly, is characterized by a clear clinical picture and requires special treatment in the department of pediatric orthopedics or pediatric surgery.